On the prediction of the reverse flow and rotating stall characteristics of high-speed axial compressors using a three-dimensional through-flow code - Righi, Mauro; Pachidis, Vassilios; Könözsy, László Z. (Elsevier, 2019)
This paper presents the development of a low-order three-dimensional through-ﬂow code created at Cranﬁeld University in the UK, named ACROSS (Axial Compressor Rotating Stall and Surge simulator), and its application to create the reverse ﬂow and rotating stall characteristics of a modern high-speed compressor. The compressor modelled is a six-stage axial-ﬂow machine, representative of a modern aero-engine high pressure compressor. The tool has been previously validated using experimental data from two low-speed compressor rigs. This article describes how the tool’s robustness and computational speed have been im proved by introducing higher-order schemes to model the circumferential ﬂuxes and the rigid movement of the ﬂow in the rotating blade rows. Further improvements include variable axial discretization, an algorithm to introduce random ﬂow perturbations in the ﬂow ﬁeld and an improved plenum model. The compressor is ﬁrst modelled in reverse ﬂow conditions to create its reverse-ﬂow characteristics and these are then compared against results from high-ﬁdelity 3D CFD simulations. Results obtained suggest that despite the presence of three-dimensional ﬂow features, 2D axi-symmetric simulations are adequate to generate the full range of reverse ﬂow characteristics of the compressor. The rotating stall characteristics at 77% and 100% corrected rotational speed are created by modelling several steady rotating stall cases in 3D. Using the code ACROSS, the complete map of the compressor modelled, comprising of forward ﬂow, reverse ﬂow and rotating stall characteristics, was created in only 5 days using 3 desktop workstations. For comparison, state-of-the-art high-ﬁdelity 3D CFD requires several days to simulate a single rotating stall case on a high performance computing facility
Keywords: Computational Fluid Dynamics (CFD); Through-ﬂow code; Reverse ﬂow; Rotating stall; High-speed axial compressors; Surge